A Unique Comparison of Tooth Extraction Before and After Emicizumab Prophylaxis in a Patient With Haemophilia A and Inhibitors - Miki Zaizen; Takahiro Yagyuu; Sachiko Yata; Hiroshi Nakamura; Mitsuhiko Imada; Nobuhiro Yamakawa (Case Reports in Dentistry)
Haemophilia A is an inherited X-linked bleeding disorder caused by Factor VIII deficiency; approximately 30% of the patients with haemophilia A develop inhibitors against Factor VIII. Emicizumab has been licenced for the prevention of bleeding in patients with haemophilia A with inhibitors and has demonstrated an 87% reduction in the annualised bleeding rate compared with on-demand therapy in patients with haemophilia A with inhibitors. Emicizumab is approved not only for patients with inhibitors but also for those without inhibitors. However, no reports exist on intraindividual comparisons of perioperative management of tooth extraction before and after emicizumab prophylaxis. This case report describes the perioperative management of similar tooth extractions in the same patient with haemophilia A with inhibitors before and after the initiation of emicizumab. This report provides a unique opportunity for intraindividual comparison of the usage of bypassing agents, postextraction bleeding, and medical costs with and without emicizumab. Furthermore, our report also supports the hypothesis that emicizumab is superior in preventing postoperative bleeding complications.